Determination of The Best Employee Using The Behavioral Anchor Rating Scale - Herman Sjahruddin; Poppy Hidayat; Irwan Moridu; I Nyoman Tri Sutaguna; Suratman (Institute of Computer Science (IOCS), 2022)
Human resource management is essential in improving the competence of human resources in the company, especially every employee, in carrying out operational activities for the company's common goals. Increasing competence requires each individual to improve performance for the company's success further and consider the provision of bonuses and allowances. An objective employee performance appraisal can produce the best employee appraisal decisions that are carried out by selecting many employees from several assessment criteria. This study aims to determine the best employee ratings by applying the Behavioral Anchor Rating Scale (BARS) method so that each parameter of employee attitude and behaviour assessment can be made on a measurable scale with rating and anchor value scales that show performance on each dimension of the four assessment criteria. The study results of 5 alternative employee candidates have successfully completed an objective assessment to produce one best employee result.